Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025676
|View full text |Cite
|
Sign up to set email alerts
|

Designing Game-Based Myoelectric Prosthesis Training

Abstract: A myoelectric prosthesis (myo) is a dexterous artificial limb controlled by muscle contractions. Learning to use a myo can be challenging, so extensive training is often required to use a myo prosthesis effectively. Signal visualizations and simple muscle-controlled games are currently used to help patients train their muscles, but are boring and frustrating. Furthermore, current training systems require expensive medical equipment and clinician oversight, restricting training to infrequent clinical visits. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…These EMG armbands have unlocked new possibilities for myoelectric control applications, which are not limited to the more traditional prosthetics market. Applications have included accessible game-based training for myoelectric prostheses [ 5 , 6 ], sport training systems [ 7 ], portable music player interfaces [ 3 ], sign language interpretation [ 8 ], and user authentication [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These EMG armbands have unlocked new possibilities for myoelectric control applications, which are not limited to the more traditional prosthetics market. Applications have included accessible game-based training for myoelectric prostheses [ 5 , 6 ], sport training systems [ 7 ], portable music player interfaces [ 3 ], sign language interpretation [ 8 ], and user authentication [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that amputees treated within a month of amputation by prosthetists and occupational therapists have a much higher rehabilitation success and return to work rate than those seen later (Bowker, 2004 ). Currently, prosthetists and occupational therapists lack tools that can be sent home with patients to allow for training between visits (Tabor et al, 2017 ). Given fiscal and geographic constraints, an additional 20 min of training per day, as observed in the current study, has the potential to improve rehabilitation success rates by providing myosite training outside of the clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Given fiscal and geographic constraints, an additional 20 min of training per day, as observed in the current study, has the potential to improve rehabilitation success rates by providing myosite training outside of the clinical environment. In both amputee and able-bodied samples described previously, the major issues with current approaches to myosite training were identified as: boring and unengaging training (Tabor et al, 2017 ); training not accessible outside the clinic (Tabor et al, 2017 ); and training does not provide patient performance metrics to a provider when used remotely by a patient (Dawson et al, 2012 ). The current system addresses each of these concerns by presenting engaging, mobile training to amputees and is associated with a cloud and web-based approach to data communication for providers.…”
Section: Discussionmentioning
confidence: 99%
“…A common limitation presented is the lack of classification robustness. To address this, recent studies provide evidence for significant performance improvement (with respect to classification accuracy and latency) achieved with DL approaches [6,41,47].…”
Section: Introductionmentioning
confidence: 99%